DESYNCHRONOSIS AND MEASURES TO PREVENT IT (American Journal of Interdisciplinary Research and Development, 2024)
A person's well-being and a high level of working capacity depend on the synchronization of the body's vital activity, i.e. the ability of the central nervous system to ensure the interaction of various periodic functions of the body and on the coincidence in time of the rhythm of the organism with the rhythm of the environment.